Identification of fungi species in the onychomycosis of institutionalized elderly Identificação de espécies fúngicas nas onicomicoses do idoso institucionalizado - Cidia Vasconcellos; Carolina Queiroz Moreira Pereira; Marta Cristina Souza; Andrea Pelegrini; Roseli Santos Freitas; Juliana Possato Takahashi (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Superficial fungal infections are caused by dermatophytes, yeasts or filamentous fungi. They are correlated to the etiologic agent, the level of integrity of the host immune response, the site of the lesion and also the injured tissue. OBJECTIVE: The purpose of this study is to isolate and to identify onychomycosis agents in institutionalized elderly (60 years old +). METHODS: The identification of the fungi relied upon the combined results of mycological examination, culture isolation and micro cultures observation under light microscopy from nail and interdigital scales, which were collected from 35 elderly with a clinical suspicion of onychomycosis and a control group (9 elderly with healthy interdigital space and nails). Both groups were institutionalized in two nursing homes in Sao Bernardo do Campo, SP, Brazil. RESULTS: The nail scrapings showed 51.40% positivity. Of these, dermatophytes were found in 44.40% isolates, 27.78% identified as Trichophyton rubrum and 5.56% each as Trichophyton tonsurans, Trichophyton mentagrophytes and Microsporum gypseum. The second more conspicuous group showed 38.89% yeasts: 16.67% Candida guilliermondii, 11.11% Candida parapsilosis, 5.56% Candida glabrata, and 5.56% Trichosporon asahii. A third group displayed 16.70% filamentous fungi, like Fusarium sp, Aspergillus sp and Neoscytalidium sp (5.56% each). The interdigital scrapings presented a positivity rate of 14.29%. The agents were coincident with the fungi that caused the onychomycosis. In the control group, Candida guilliermondii was found at interdigital space in one person. CONCLUSION: Employing a combination of those identification methods, we found no difference between the etiology of the institutionalized elderly onychomycosis from that reported in the literature for the general population. FUNDAMENTOS: As infecções fúngicas superficiais se correlacionam com o agente etiológico, a resposta imune do hospedeiro, o local da lesão e o tecido lesado, sendo causadas por dermatófitos, leveduras ou fungos filamentosos. OBJETIVO: O objetivo é isolar e identificar os agentes das onicomicoses em idosos institucionalizados. MÉTODO: A identificação dos fungos baseou-se nos resultados combinados do exame micológico, isolamento em cultura e da observação de microculturas sob microscopia de luz, do material subungueal e escamas interdigitais, coletado de 35 idosos com suspeita clínica de onicomicose e de um grupo controle (9 idosos com espaço interdigital e unhas saudáveis). Ambos os grupos eram institucionalizados em duas casas de assistência em São Bernardo do Campo, SP, Brasil. RESULTADOS: As unhas raspadas apresentaram 51,40% de positividade. Os dermatófitos foram encontrados em 44,40% de isolados, sendo 27,78% identificados como Trichophyton rubrum e 5,56%, cada, como Trichophyton tonsurans, Trichophyton mentagrophytes e Microsporum gypseum. O segundo grupo mais frequente (38,89%) foi o de leveduras, identificadas como 16,67% Candida guilliermondii, 11,11% Candida parapsilosis, 5,56% Candida glabrata e 5,56% Trichosporon asahii. Um terceiro grupo exibia 16,70% fungos filamentosos, como Fusarium sp, Aspergillus sp e Neoscytalidium (5,56% de cada). Os raspados interdigitais exibiram positividade de 14,29%. Os agentes foram coincidentes com os fungos que causaram a onicomicose. No grupo controle, a Candida guilliermondii foi identificada no espaço interdigital em apenas uma pessoa. CONCLUSÃO: Empregando-se a combinação destes métodos de identificação, não houve diferença entre a etiologia da onicomicose dos idosos institucionalizados daquela relatada na literatura para a população em geral.